Do majority shareholder control deviation results in financial constraints? - Igor Bernardi Sonza; Alberto Granzotto (Enfoque)
Purpose: This study aims to analyze how the moral hazard of the majority shareholder results in financial constrainsts for Brazilian companies listed on Brazil, Bolsa and Balcão (B3). Method: we used the Ordinary Least Squares (OLS) to compare the cash flow sensitivity of cash for firms that have high control deviations control, presenting high moral hazard (constraints), with companies that have low control deviations, presenting low moral hazard (no restrictions). Originality/Relevance: The originality of the research resides in the evidence that the deviation of shareholding control can be understood as a source of credit restriction, putting in check a particular and idiosyncratic source in emerging markets such as Brazil. Results: our first result evidenced that, in historical terms, the control deviation declined significantly. On the other hand, the results reveal that the moral hazard of the majority shareholder, represented by the deviation of control, results in financial restrictions of Brazilian companies listed on B3. Theoretical/methodological/practical contributions: the main implication of the research is to reveal idiosyncratic sources of credit in Brazil, since the majority shareholder control deviation (MSCD) reflects the weak legal protection for minority shareholders and creditors (civil law). This research helps capital market investors in countries with weak legal protections to choose companies that are concerned about governance issues, as well as companies to understand that such deviations can be harmful to corporate debt.